Association Between Public Self-Consciousness, Psychological Wellbeing and Physical Health Among University Students in Sialkot - Salbia Abbas, Fajar Naseer, Fizza Aqeel, Mahnoor Zahid, Mamoona Abid, Farah Ashiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this study was to find the relationship among public self-consciousness, physical health and psychological well-being among university students in Sialkot. Methods: Data was collected from 200 university students belong to different universities of Sialkot through survey method. Results: Results revealed that there is negative relationship of public self-consciousness with physical health and psychological well-being. Conclusion:Public appearance self-consciousness is a reality that has affected every single person across the world but its effects vary in every person due to individual differences. So, self-consciousness about public appearance is highly but negatively correlated to physical health. There is also a negative correlation between public appearance self-consciousness and psychological well-being. It greatly affects female population worldwide than males. Keywords: Public self-consciousness, physical health, psychological well-being, university students